Isolation Of Polycyclic Aromatic Hydrocarbons Degrading Pgpr From A Oil Products Contaminated Site In Hyderabad, Telangana State, India - M. POORNACHANDER RAO; A.B. RAJITHASRI; K.SAGAR; K. SATYAPRASAD (International Journal of Pharma and Bio Sciences, 2015)
Rhizoremediation of polycyclic aromatic hydrocarbons (PAHs) with aid of Plant Growth Promoting Rhizobacteria (PGPR) is a novel, effective and emerging method in advance research of green chemistry. In the present study, the authors have isolated 26 PAHs degrading bacteria from PAHs contaminated soil samples of plants growing in premises of oil products manufacturing industries located in Cherlapally, Hyderabad. Depending upon growth of the isolates in Minimal salt medium (MSM) enriched with test PAHs phenanthrene, anthracene and pyrene effective PAHs degrading bacteria were identified. The same isolates were screened for the production of PGPR traits such as Indole acetic acid, hydrogen cyanide, ammonia and enzymes like phosphatases, proteases, cellulases, chitinases etc. Based on PAHs degradation and PGPR tests, the most effective PAHs degrading PGPR strain P14 was selected for further work. This isolate is gram positive, undulate, spore forming bacillus and biochemically positive for the reactions of ornithine utilization, nitrate reduction, citrate utilization, Voges Proskaure’s test, methyl red test, cytochrome oxidase, catalase. This strain utilized sugars like glucose, lactose, saccharose, mellibiose, raffinose and trehalose on the characterization. In molecular characterization with 16rDNA sequencing the strain has showed maximum similarity with Bacillus cereus. Based upon all the characterization methods we named it as Bacillus cereus CPOU13.